1998
DOI: 10.1038/sj.bjp.0702220
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological characterization of the human vasopressin receptor subtypes stably expressed in Chinese hamster ovary cells

Abstract: 1 Three subtypes of human (h) arginine vasopressin (AVP) receptors, hV 1A , hV 1B and hV 2 , were stably expressed in Chinese hamster ovary (CHO) ] i or cyclic AMP response was similar to that observed in radioligand binding assays. 5 In conclusion, we have characterized the pharmacology of human cloned V 1A , V 1B and V 2 receptors and used these to determine the anity, selectivity and potency of nonpeptide AVP receptor antagonists. Thus they may prove to be a valuable tool in further examination of the phy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
33
0
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(40 citation statements)
references
References 35 publications
6
33
0
1
Order By: Relevance
“…AVP stimulation of WT-V 2 R expressing cells promoted cAMP production with an EC 50 of 1.54 ± 0.16 n M , in accordance with a previous report [15]. In cells expressing V88M-V 2 R, the dose-dependent AVP-stimulated cAMP production was found to be right-shifted by more than 100-fold compared to WT-receptor expressing cells with an EC 50 of 248 ± 45 n M (fig.…”
Section: Resultssupporting
confidence: 78%
“…AVP stimulation of WT-V 2 R expressing cells promoted cAMP production with an EC 50 of 1.54 ± 0.16 n M , in accordance with a previous report [15]. In cells expressing V88M-V 2 R, the dose-dependent AVP-stimulated cAMP production was found to be right-shifted by more than 100-fold compared to WT-receptor expressing cells with an EC 50 of 248 ± 45 n M (fig.…”
Section: Resultssupporting
confidence: 78%
“…It mediates vasoconstriction, vascular smooth muscle cell proliferation [8], glycogen metabolism, platelet aggregation, positive inotropy, hypertension and coronary vasospasm. Furthermore, the V1a-receptor promotes hypertrophic growth of myocardial cells [9][10]. Antagonism of V1a-receptors may result in increased cardiac output, reduced total peripheral resistance, reduced mean arterial blood pressure and inhibition of vasopressin-induced protein synthesis of cardiomyocytes.…”
Section: Introductionmentioning
confidence: 98%
“…Moreover, the IC 50 value in a cell culture assay is higher for conivaptan (44) than for NOX-F37 (14.3 nM vs. 6.1 nM), which is further strengthened by the fact that the IC 50 of NOX-F37 was determined in an Ϸ4-fold less-sensitive cell assay (EC 50 Ϸ 5 nM) compared with conivaptan (EC 50 Ϸ 1.3 nM; ref. 37). It can be concluded that NOX-F37 might block AVP-induced V 1a receptor activation very efficiently and could reduce AVP-mediated remodeling in the heart of CHF patients accordingly.…”
Section: Discussionmentioning
confidence: 99%
“…Most advanced are tolvaptan, described as a specific V 2 receptor antagonist, and conivaptan, a dual V 1a and V 2 receptor antagonist. Both antagonists are benzazepine derivatives that show inhibition constants to the human V 2 and V 1a receptors of 0.4 and 12.3 nM for tolvaptan and 1.1 and 6.3 nM for conivaptan, respectively (36,37). In vivo efficacy was demonstrated for both antagonists in preclinical and clinical studies (7,(38)(39)(40).…”
Section: Discussionmentioning
confidence: 99%